THE INFLUENCE OF SUPERVISION, WORKLOAD AND MOTIVATION ON THE WORK PRODUCTIVITY OF THE PACKING DEPARTMENT AT PT. X BANDUNG REGENCY - Merry Fithriani (SEAN Institute, 2022)
The purpose of this study is to determine the effect of supervision, workload and motivation on the work productivity of the packing section at PT. X Kabupaten Bandung. Where independent variables consist of photocariths, workloads, and motivation. While the dependent variable is work productivity. This study uses a quantitative method, where this instrument is in the form of observation, interviews, and questionnaires. The population in this study is the employees of the packing section at PT. X Kabupaten Bandung. Samples taken as many as 72 employees. The analysis used in this study includes validity test, reliability test, descriptive analysis, classical assumption test, multiple linear regression analysis, partial test, simultaneous test and determination test.